Attainment of low disease activity and remission targets reduces the risk of severe flare and new damage in childhood lupus. (11th December 2021) - Smith, Eve M D; Tharmaratnam, Kukatharmini; Al-Abadi, Eslam; Armon, Kate; Bailey, Kathryn; Brennan, Mary; Ciurtin, Coziana; Gardner-Medwin, Janet; Haslam, Kirsty E; Hawley, Daniel; Leahy, Alice; Leone, Valentina; et al.
Abstract: Objectives: To assess the achievability and effect of attaining low disease activity (LDA) or remission in childhood-onset SLE (cSLE). Methods: Attainment of three adult-SLE derived definitions of LDA (LLDAS, LA, Toronto-LDA), and four definitions of remission (clinical-SLEDAI-defined remission on/off treatment, pBILAG-defined remission on/off treatment) was assessed in UK JSLE Cohort Study patients longitudinally. Prentice–Williams–Petersen gap recurrent event models assessed the impact of LDA/remission attainment on severe flare/new damage. Results: LLDAS, LA and Toronto-LDA targets were reached in 67%, 73% and 32% of patients, after a median of 18, 15 or 17 months, respectively. Cumulatively, LLDAS, LA and Toronto-LDA was attained for a median of 23%, 31% and 19% of total follow-up-time, respectively. Remission on-treatment was more common (61% cSLEDAI-defined, 42% pBILAG-defined) than remission off-treatment (31% cSLEDAI-defined, 21% pBILAG-defined). Attainment of all target states, and disease duration (>1 year), significantly reduced the hazard of severe flare ( P < 0.001). As cumulative time in each target increased, hazard of severe flare progressively reduced. LLDAS attainment reduced the hazard of severe flare more than LA or Toronto-LDA ( P < 0.001). Attainment of LLDAS and all remission definitions led to a statistically comparable reduction in the hazards of severe flare ( P > 0.05). Attainment of all targets reduced the hazards of new damage ( P < 0.05). Conclusions: This is the first study demonstrating that adult-SLE-derived definitions of LDA/remission are achievable in cSLE, significantly reducing risk of severe flare/new damage. Of the LDA definitions, LLDAS performed best, leading to a statistically comparable reduction in the hazards of severe flare to attainment of clinical remission.